Meningkatkan Kekuatan Penyelidikan: Memahami Resistivitas di Kelas Fisika: Penerapan Hukum Ohm dalam Pembelajaran Berbasis Kelas - Aprillya, SonjaWidya; Hafidudin, Ahmad; Nisa, Wifa Alifatun; Mutia, azrisa; Malik, Adam (EduFisika: Jurnal Pendidikan Fisika, 2025)
Abstracts This study aims to explore the effectiveness of inquiry-based learning in improving students’ conceptual understanding of electrical resistivity within the context of physics education. Many students struggle to comprehend the relationship between resistance, length, and cross-sectional area of conductors, often due to abstract instruction and a lack of hands-on experience. To address this, a classroom-based experimental activity was designed where students investigated resistivity using Ohm’s Law and direct measurements of voltage and current. The participants, consisting of tenth-grade science students, conducted experiments using wires of varying dimensions and calculated resistivity values. Pretest and posttest assessments were administered to evaluate conceptual gains, and the results showed a moderate to high increase in understanding based on normalized gain (N-gain) scores. The findings highlight that inquiry-based methods enable students to engage in authentic scientific practices such as observation, data collection, and analysis. The novelty of this study lies in its integration of low-cost, accessible experiments into structured inquiry learning, proving that conceptual depth can be achieved without sophisticated equipment. The results suggest that applying inquiry-based strategies in physics classrooms can enhance students’ scientific literacy, problem-solving abilities, and critical thinking, contributing to meaningful and effective science education.